Physically Secure Wearable–Wearable Through-Body Interhuman Body Communication - Yang, David; Maity, Shovan; Sen, Shreyas (Frontiers in Electronics, 2022)
Human Body Communication (HBC) has recently emerged as an alternative method to connect devices on and around the human body utilizing the electrical conductivity properties of the human body. HBC can be utilized to enable new interaction modalities between computing devices by enhancing the natural interaction of touch.It also provides the inherent benefit of security and energy-efficiency compared to a traditional wireless communication such as Bluetooth, making it an attractive alternative. However, most state of the art HBC demonstrations show communication between a wearable and an earth ground connected device and there have been very few implementations of HBC systems demonstrating communication between two wearable devices. Also, most of the HBC implementations suffer from the problem of signal leakage out of the body which enables communication even without direct contact with the body. In this paper we present Bodywire which uses Electro-Quasistatic HBC (EQS-HBC) technique to enable communication between two wearable devices and also confine the signal to a very close proximity to the body. We characterize the human body channel loss under different environment (office desk, laboratory, outdoors), posture, body location conditions to ascertain the effect of each of these on the overall channel loss. The measurement results show that the channel loss varies within a range of 7dB across all different posture, environmental condition and body location variation, illustrating the dynamic range of signal available at the input of any receiver. Leakage measurements are also carried out from the devices to show the distance over which the signal is available away from the body to illustrate the security aspect of HBC and show its effect on the channel loss measurements. For the first time a through-body inter-human channel loss characterization is presented. Finally, a demonstration of secure inter-human information exchange between two battery operated wearable devices is shown through the Bodywire prototype, which shows the smallest form factor HBC demonstration according to the authors’ best knowledge